Rapid detection of toxic dinoflagellate, alexandrium minutum (dinophyceae) using whole-cell fluorescence in situ hybridization (fish) - Yek, Leh Hie (Universiti Malaysia Sarawak, UNIMAS, 2012)
Harmful algal blooms (HABs) are phenomena known as sudden increase in microalgal population that cause not only human seafood poisoning but also impact to the marine ecosystem. The dinoflagellates particularly species of Alexandrium have been known as producers of paralytic shellfish poisoning (PSP) toxins, a type of sodium blocking neurotoxins collectively called saxitoxin (STX). Species identification in the genus was commonly done under conventional light microscope. However variation in morphological characteristics used in delineating species is often hard to detect which requires taxonomic expertise. Hence, this study adopts a molecular detection approach to rapidly detect the species of Alexandrium by using whole-cell fluorescence in situ hybridization (FISH). Ribosomal RNA-targeted oligonucleotide DNA probe targeting the toxic Alexandrium minutum were designed in silico. Specificity and accessibility of designed probes were further verified in silico comparing parameters that influenced the hybridzation kinetics. An A. minutum species-specific probe region was successfully identified, and designated as L-S-Amin-569-A-18. The probe was synthesized and tested on clonal cultures of A. minutum. Samples were fixed and then underwent wholecell FISH protocol prior to observation under an epi fluorescence microscope. Optimization on FISH procedure was conducted to determine the optimum hybridization conditions. The result showed that the DNA probe had high specificity towards A. minutum with no cross-reactivity towards other Alexandrium (A. tamiyavanichii, A. tamutum and A. affine). The FISH protocol had been proven as rapid detection tool for A. minutum in regional of Malaysia. Hence, this approach is proposed to be adopted in the national harmful algal monitoring.